Analisis Jaringan Dinamis Informasi dan Sentimen Berita Ekonomi - Prasetyo, Nur Cahyo Agung; Rahmanto, Andre Noevi; Sudarmo, Sudarmo (Seminar Nasional Official Statistics, 2024)
This study examines the dissemination and perception of economic information in Indonesian online media, focusing on detik.com and cnbcindonesia.com. The complexity of economic information presented in online media can hinder public understanding and lead to misinterpretation, which impacts decision-making processes. Using sentiment analysis and Dynamic Network Analysis (DNA), this research aims to understand how news framing influences public perception of economic data, particularly from the Badan Pusat Statistik (BPS). The methodology includes news collection, text preprocessing, and sentiment classification, analyzing news articles published from September to November 2023. The findings reveal a predominance of neutral sentiment in economic reporting, underscoring the importance of accurate and accessible economic reporting for informed decision-making.